TRANSFORMING CONTRACT ADMINISTRATION COURSE THROUGH INTERACTIVE TEACHING AND LEARNING FOR QUANTITY SURVEYING UNDERGRADUATES - Wan Mohd Nurdden Wan Muhammad; Siti Suhana Judi; Zulkhairy Affandy Mohd Zaki; Zulhabri Ismail (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
In recent years, the landscape of higher education has increasingly embraced interactive learning methods to enhance student engagement and learning outcomes. This study evaluates the effectiveness of interactive activities integrated into a Professional Practice course at Universiti Teknologi MARA (UiTM). Employing a quantitative research design, data were collected from final-year students in the Bachelor (Hons) Quantity Surveying program using a structured questionnaire. The analysis focused on students’ perceptions of the clarity, usefulness, and timing of learning materials and activities, as well as the effectiveness of engagement strategies. The findings reveal high mean scores for the clarity and utility of the materials, indicating that the course design effectively communicates content in a practical and comprehensible manner. Additionally, students rated the timing of activities positively, suggesting a well-aligned instructional approach. The study also highlighted a strong perception of engagement, with high scores for both overall student involvement and the interactive nature of course activities. This suggests that gamification tools and the flipped classroom model significantly contribute to maintaining student interest and promoting active participation. The results underscore the success of interactive learning strategies in creating an engaging and effective educational environment. The consistent positive feedback reflects the effectiveness of these pedagogical methods in enhancing student learning experiences. The study concludes that continued innovation and refinement of interactive learning practices are crucial for further improving educational outcomes and preparing students for future challenges. , , , ,